2018
DOI: 10.1161/strokeaha.117.020035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Visceral Infarction and Ischemic Stroke Subtype

Abstract: Background and Purpose Most cryptogenic strokes are thought to have an embolic source. We sought to determine whether cryptogenic strokes are associated with visceral infarcts, which are usually embolic. Methods Among patients prospectively enrolled in the Cornell AcutE Stroke Academic Registry (CAESAR), we selected those with a contrast-enhanced abdominal computed tomography (CT) scan within 1 year of admission. Our exposure variable was adjudicated stroke subtype per the TOAST classification. Our outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Characteristics of CAESAR have been published previously. (17) Patients were included if they were 18 to 65 years of age, were hospitalized for an acute ischemic stroke of any subtype from 2011 through 2015, and had any laboratory testing for thrombophilia within 6 months of index stroke. Standard thrombophilia testing at our institution includes serum evaluation for antiphospholipid syndrome comprising the anticardiolipin and anti-beta-2 glycoprotein-1 antibodies (IgG and IgM isotypes) and lupus anticoagulant; Factor V Leiden gene mutation; prothrombin gene G202010A mutation; protein C, protein S, and antithrombin deficiencies; increased homocysteine; and methylenetetrahydrofolate reductase (MTHFR) gene mutation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of CAESAR have been published previously. (17) Patients were included if they were 18 to 65 years of age, were hospitalized for an acute ischemic stroke of any subtype from 2011 through 2015, and had any laboratory testing for thrombophilia within 6 months of index stroke. Standard thrombophilia testing at our institution includes serum evaluation for antiphospholipid syndrome comprising the anticardiolipin and anti-beta-2 glycoprotein-1 antibodies (IgG and IgM isotypes) and lupus anticoagulant; Factor V Leiden gene mutation; prothrombin gene G202010A mutation; protein C, protein S, and antithrombin deficiencies; increased homocysteine; and methylenetetrahydrofolate reductase (MTHFR) gene mutation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 , 11 , 16 Many of these patients were also found to have other systemic evidence of thromboembolic disease 39 , 40 and visceral infarction—a phenomenon that is known to be associated with cardioembolic and cryptogenic strokes. 41 …”
Section: Stroke As a Complication Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Visceral infarctions are often incidentally detected in patients with acute ischemic stroke. Recently, we have reported that visceral infarctions are more often detected in patients with cardioembolic or cryptogenic stroke subtypes [3]. Little is known about the mechanisms and significance of these commonly detected lesions.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Among an autopsy study of patients with fatal ischemic stroke, onefifth had evidence of visceral infarctions; renal and splenic infarctions were the most frequent types of visceral infarctions [2]. Visceral infarctions may be a marker of a Cerebrovasc Dis 2020;49:316-320 DOI: 10.1159/000508826 central embolic source as they are more often detected in patients with cardioembolic stroke or embolic stroke of undetermined source [3]. Despite their frequency, the clinical significance of visceral infarctions remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%